2016
DOI: 10.1186/s13068-016-0670-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome and methylome of the oleaginous diatom Cyclotella cryptica reveal genetic flexibility toward a high lipid phenotype

Abstract: BackgroundImprovement in the performance of eukaryotic microalgae for biofuel and bioproduct production is largely dependent on characterization of metabolic mechanisms within the cell. The marine diatom Cyclotella cryptica, which was originally identified in the Aquatic Species Program, is a promising strain of microalgae for large-scale production of biofuel and bioproducts, such as omega-3 fatty acids.ResultsWe sequenced the nuclear genome and methylome of this oleaginous diatom to identify the genetic trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
82
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 89 publications
4
82
0
7
Order By: Relevance
“…In P. infestans and P. sojae , we observed a bimodal distribution pattern of 6mA enriched regions flanking the TSS, but with a clear depletion at the TSS itself and immediately downstream. This pattern resembles 6mA methylation described for the green algae Chlamydomonas 41 . Our comparisons of transcriptome and methylome data suggest that 6mA is negatively correlated with gene expression in the two Phytophthora species.…”
Section: Discussionsupporting
confidence: 83%
“…In P. infestans and P. sojae , we observed a bimodal distribution pattern of 6mA enriched regions flanking the TSS, but with a clear depletion at the TSS itself and immediately downstream. This pattern resembles 6mA methylation described for the green algae Chlamydomonas 41 . Our comparisons of transcriptome and methylome data suggest that 6mA is negatively correlated with gene expression in the two Phytophthora species.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, the sequencing of multiple diatom genomes (P. tricornutum, T. pseudonana, and, more recently, Cyclotella cryptica) has provided potential for studies of chitin/chitosan biosynthetic pathways (Armbrust et al, 2004;Bowler et al, 2008;Traller et al, 2016). However, the analysis of biological function, especially for CDA, is largely lacking, and the distinct features of chitin/chitosan in pennate and centric diatoms remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…is the first large-scale and systematic approach of HGT detection across all available sequenced 258 diatoms. While some previous studies were based on phylogenetics 7,30 , most relied purely on sequence 259 homology searches 24,25,27 , while it has been shown that the degree of gene similarity does not 260 necessary necessarily reflect phylogenetic relationships 65,66 . Although HGT had been previously 261 predicted in P. multistriata, C. cryptica, T. oceanica and twice in P. tricornutum, only a fraction of HGT 262 genes were confirmed across these studies, going from 6 to 45% ( Figure S12).…”
Section: Discussion 255mentioning
confidence: 99%
“…In the early 22 Cretaceous, between 150 and 130 million years ago, diatoms split into the centric and pennate lineage. 23 Several whole-genome sequences of representatives from polar centrics (Thalassiosira pseudonana 23 , 24 Thalassiosira oceanica 24 , Cyclotella cryptica 25 ), araphid pennates (Synedra acus 26 ) and raphid pennates 25 (Phaeodactylum tricornutum 7,27 , Fistulifera solaris 28 , Fragilariopsis cylindrus 29 , Pseudo-nitzschia 26 multistriata 30 ) have become available in recent years, which allows the analysis of the evolutionary 27 history within diatoms. It is not fully understood how HGT has contributed to the ecological success of 28 this environmentally important group of organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation